1992
DOI: 10.2134/agronj1992.00021962008400050022x
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Concentrations of Nitrate in Cornstalks at Maturity

Abstract: The concentration of NO−3 in the lower portion of cornstalks at physiological maturity has been proposed as the basis for evaluating the N status of corn (Zea mays L.). Here we refine estimates of the optimal range in NO−3 concentrations for this test by using relevant economic scenarios that include 900 plot‐years of new data as well as 450 plot‐years reported earlier. The results showed that rainfall had little effect on concentrations of NO−3 identified as being optimal. However, calculations showed that op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
146
3
5

Year Published

1997
1997
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(164 citation statements)
references
References 9 publications
10
146
3
5
Order By: Relevance
“…If samples are collected closer to the soil than described in the original procedure (< 15 cm above the soil), the resulting analyses will likely produce greater nitrate-N concentrations. As a result, the critical values suggested by Binford et al (1990Binford et al ( , 1992) may have to be adjusted upward. Data from this initial study with an adequate to excessive N rate (N application, yield stalk nitrate-N, 3254 mg ) suggests critical values may need to be increased by about 35% (comparison of S+2 to S+l in Table 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If samples are collected closer to the soil than described in the original procedure (< 15 cm above the soil), the resulting analyses will likely produce greater nitrate-N concentrations. As a result, the critical values suggested by Binford et al (1990Binford et al ( , 1992) may have to be adjusted upward. Data from this initial study with an adequate to excessive N rate (N application, yield stalk nitrate-N, 3254 mg ) suggests critical values may need to be increased by about 35% (comparison of S+2 to S+l in Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…In the test, 20-cm sections of corn stalks (between 15 and 35 cm above the soil) are collected from several plants, dried, ground, and analysed for nitrate-N. Nitrate-N concentrations less than dry stalk tissue indicated that available N limited grain yield whereas concentrations greater than indicated excessive N was available to the crop (Binford et al, 1992). Other researchers have evaluated the test and concurred that stalk nitrate concentrations greater than indicated that excessive N was available to the crop (Varvel et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Diferentemente, o tratamento na ausência de zeólita apresenta variações mais altas entre as produções, uma vez que a produção de MS está ligada ao acúmulo de nitrogênio. 32 Consideram-se dois aspectos para aplicação de uma fonte de nitrogênio eficiente, aproveitamento e perda por lixiviação; já que menos de 50% é utilizado pelas culturas, o percentual de aproveitamento foi calculado com base no teor de nitrogênio total na matéria seca, visto que as plantas absorvem predominantemente nitrogênio oriundo do solo. 33 As médias da produção de matéria seca para diferentes fertilizantes nitrogenados e quantidade de nitrogênio aplicado no solo, presente na parte aérea e lixiviado de cada tratamento, são apresentadas nas Tabelas 2 e 3, respectivamente.…”
Section: Resultsunclassified
“…Os testes de capacidade levam em consideração, para estimar a disponibilidade de N parâmetros ambientais, o histórico da área e as propriedades do solo (Klausner et al, 1993). Já os testes de intensidade baseiam-se na quantidade de N mineral presente no solo, por meio de testes de pré-semeadura (Schröder et al, 2000), de pré-aplicação de N em cobertura (Binford et al, 1992), e de pós-colheita (Sims et al, 1995).…”
Section: Introductionunclassified
“…Entre os parâmetros de planta mais utilizados como indicadores do nível de N, estão a concentração de NO 3 -e a concentração de N total (Binford et al, 1992), e a intensidade da cor verde da folha. Este último pode ser determinado por meio de mensurações de refletância (Ma et al, 1996) e de absorção (Waskom et al, 1996;Sunderman et al, 1997;Varvel et al, 1997;Bullock & Anderson, 1998;Argenta et al, 2001).…”
Section: Introductionunclassified